The Influence of Sexual Orientation and Gender Identity on the Otolaryngology Residency Experience - Walter M. Jongbloed; Hillary A. Newsome; Lawrence Kashat; Kourosh Parham; Erynne A. Faucett; Chia‐Ling Kuo; Kelin Zhong; Katherine R. Kavanagh (OTO Open, 2025)
Abstract Objective This study examines the influence of sexual orientation and gender on residents' experiences in US Otolaryngology residency programs. This study assesses the prevalence of bullying, sexual harassment, discrimination, homophobic remarks and evaluates the workplace environment, well‐being, and impact of LGBTQ+ residents/faculty on rank list. Study Design A 26‐question REDCap survey was distributed to all US Otolaryngology residencies. Methods The survey was distributed to program directors over three months. Responses were compared between groups (sexual orientation and gender) using Fisher's exact test (5% significance level). Results The response rate was 5.9% (104 responses), 15.5% identified as LGBTQ+. LGBTQ+ residents felt less comfortable disclosing relationships to attendings than heterosexuals (68.8% versus 85.3%, P = .005). LGBTQ+ and female respondents perceived a worse residency environment (P < .05). LGBTQ+ residents were less satisfied with their decision to pursue Otolaryngology (75% vs 95.4%, P = .044) and more likely to consider leaving their program (25% vs 6.9%; P = .047). An LGBTQ+ faculty member or resident positively impacted rank lists for LGBTQ+ residents (43.8% vs 12.6%, P = .007; 50% vs 16.1% P = .005). Women reported more discrimination and sexual harassment than men (78.4% vs 14.8%; P < .001; 31.9% vs 11.1%; P = .014, respectively). Conclusion LGBTQ+ and female respondents perceive a worse residency environment. LGBTQ+ residents are less comfortable disclosing relationships to attendings, less satisfied with their decision to pursue Otolaryngology, more likely to consider leaving programs, and desire representation. Women are at increased risk of sexual harassment and discrimination.